STRATEGI DALAM UPAYA MEMPERBAIKI KETERLAMBATAN PENYERAPAN ANGGARAN BELANJA PADA PEMERINTAH KOTA BOGOR - Gustawan Rachman; Ma'mun Sarma; Dwi Rachmina (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2025)
ABSTRACT The absorption of the budget expenditures by the Bogor City Government has consistently experienced delays in recent years. Data collected from the period between 2011 and 2018 indicates that the average Surplus at the End of the Year (SiLPA) for the Bogor City Government has consistently been worse than the average SiLPA for districts and cities in the West Java Province. Additionally, data from 2016 to 2018 shows persistent delays in budget expenditure absorption, along with deviations between the scheduled and actual absorption of budget expenditures. The objective of this research is to formulate a strategy to improve the performance of budget expenditure absorption by the Bogor City Government using the Analytic Hierarchy Process method. Based on the results of the Analytical Hierarchy Process, it is evident that the main constraints in improving budget expenditure absorption are both internal and external interventions. The primary strategy to address the delay in budget expenditure absorption involves enhancing the quality of budget planning activities and procurement of goods and services. Keywords: AHP, budget expenditure, absorption, strategy